Digital filters design for signal and image processing - Najim, Mohamed (Digital signal and image processing series., 2006)
Dealing with digital filtering methods for 1-D and 2-D signals, this book provides the theoretical background in signal processing: z-transform, Shannon sampling theorem and fast Fourier transform. An entire chapter is devoted to the design of time-continuous filters which provides a useful preliminary step for the analog-to-digital filter conversion. Digital Filters Design for Signal and Image Processing focuses on the main approaches to design Finite Impulse Response (FIR) and Infinite Impulse Response (IIR) filters. Bi-dimensional digital filtering, i.e. the image filtering, is investigated.